Apoptotic Effects of Quercitrin on DLD-1 Colon Cancer Cell Line - Çinçin, Zeynep Birsu; Ünlü, Miray; Kıran, Bayram; Bireller, Elif Sinem; Baran, Yusuf; Çakmakoğlu, Bedia (Springer Science and Business Media LLC, 2014)
Quercetin, which is the most abundant bioflavonoid compound, is mainly present in the glycoside form of quercitrin. Although different studies indicated that quercitrin is a potent antioxidant, the action of this compound is not well understood. In this study, we investigated whether quercitrin has apoptotic and antiproliferative effects in DLD-1 colon cancer cell lines. Time and dose dependent antiproliferative and apoptotic effects of quercitrin were subsequently determined by WST-1 cell proliferation assay, lactate dehydrogenase (LDH) cytotoxicity assay, detection of nucleosome enrichment factor, changes in caspase-3 activity, loss of mitochondrial membrane potential (MMP) and also the localization of phosphatidylserine (PS) in the plasma membrane. There were significant increases in caspase-3 activity, loss of MMP, and increases in the apoptotic cell population in response to quercitrin in DLD-1 colon cancer cells in a time- and dose-dependent manner. These results revealed that quercitrin has antiproliferative and apoptotic effects on colon cancer cells. Quercitrin activity supported with in vivo analyses could be a biomarker candicate for early colorectal carcinoma.
Keywords: Membrane Potential, Mitochondrial; Time Factors; Dose-Response Relationship, Drug; L-Lactate Dehydrogenase; Caspase 3; Quercitrin; Antineoplastic Agents; Apoptosis; Adenocarcinoma; In Vitro Techniques; Antioxidants; Colon cancer; Antineoplastic agent; Cell Line, Tumor; Colonic Neoplasms; Humans; Quercetin; Antiproliferative; Cell Proliferation; 3. Good health